The practical application of Vectar Processed densities in proving the lateral continuity of coal Zones and Samples in the Ellisras Basin, South Africa in support of effective Mineral Resource adjudication - Camisani-Calzolari, Ferdinando Roux (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.